Risk of cardiac rupture among elderly patients with diabetes presenting with first acute myocardial infarction - Zu, Xiaolin; Jin, Yanyan; Zeng, Yaping; Li, Peng; Gao, Hai (Frontiers in Endocrinology, 2023)
Objective We aimed to analyze the risk of cardiac rupture (CR) in aged diabetic patients with acute ST-segment elevated myocardial infarction (STEMI) who were followed up for one month, and analyze its independent risk factors.Methods A total of 3063 aged patients with first onset STEMI admitted to Beijing Anzhen Hospital from January 2001 to December 2020 were retrospectively included.There were 2020 patients without diabetes mellitus (DM) and 1043 patients with DM.We used propensity scores matching (PSM) method to balance baseline exposure factors between patients with or without DM, and all were divided the DM group (1043 cases) and the non-DM group (1043 cases) after the PSM. The primary outcome was CR. After PSM, the baseline clinical data were similar between the DM and non-DM group (all P>0.05). During 1 month of follow-up, there were 55 (2.64%) cases of CR, most occurred within 48h after admission (40 cases). Among the 55 cases, 11(0.53%) had papillary muscle rupture, 18(0.86%) had ventricular septum perforation, and 26(1.25%) had free wall rupture. Kaplan-meier survival analyses detected that the DM group was associated with significantly increased risk of CR (3.36% vs. 1.92%, HR=1.532, 95% CI: 1.054-2.346, P=0.030), ventricular septum perforation (1.05% vs. 0.67%, HR=1.464, 95% CI: 1.021-2.099, P=0.038) and free wall rupture (1.63% vs. 0.86%, HR=1.861, 95% CI: 1.074-3.225, P=0.027) than those in the non-DM group. Among the 2031 aged STEMI patients without CR, 144 cases (6.90%, 144/2086) died; and among the 55 patients with CR, 37 cases (1.77%, 37/2086) died due to CR. Therefore, twenty percent (20.44%, 37/181) of death was due to CR. Multivariate Cox regression analysis indicated that DM (HR=1.532, 95%CI: 1.054-2.346), age (HR=1.390, 95%CI: 1.079-1.791), female (HR=1.183, 95%CI: 1.049-1.334), troponin I (HR=1.364, 95%CI: 1.108-1.679), brain natriuretic peptide (HR=1.512, 95%CI: 1.069-2.139), revascularization (HR=0.827, 95%CI: 0.731-0.936) and β-receptor blocker (HR=0.849, 95%CI: 0.760-0.948) were independent risk factors of CR (all P<0.05).Conclusions DM as well as a few other factors, are independent determinants of CR.CR is not a rare event among the aged STEMI patients and twenty percent of deaths are due to CR. However, large sample-sized studies are warranted to confirm these findings.